Synthesis and photopolymerization kinetics of linear alicyclic urethane acrylate macromonomer in presence of reactive diluents - Harikrishna, Reghunathan; Bhosle, Sonali Madhavrao; Ponrathnam, S.; Rajan, C. R. (Journal of Materials Science, 2011)
This study deals with the photopolymerization of a macromonomer in the presence of reactive diluents using Photo Differential Scanning Calorimetry or Photo DSC. The kinetic profiles of these systems showed that the rate of photopolymerization rapidly increases at very early stages of the reaction. The rate of reaction was further found to increase with the addition of crosslinking agents. The addition of trifunctional crosslinking agent to the macromonomeric formulation resulted in a higher polymerization rate and conversion than that of a difunctional crosslinking agent. From the heat flow profiles, the kinetic parameters such as induction time, time to attain peak maximum, rate of maximum polymerization, and final conversion were noted for all the formulations. The initiation of photopolymerization was found to depend on the functionality while the in situ viscosity controlled the time scale for reaction diffusion which resulted in varying levels of conversions. Other parameters such as effect of temperature and concentration of photoinitiator on photocuring kinetics are also discussed.

Amino functionalized oligo polyimides with enhanced storage stability - Dwivedi, Mayank; Rao, Locanindi Hari Sarvothama; Mohan, Srinivasulu Reddy Krishna; Dhanasekharan, Janakiraman; Rao, Bevara Madhusudana; Kumar, Sriperambudur Rajesh; Ponrathnam, Surendra; Rajan, Chelanattukizhakkemadath Raman; Tayal, Rajiv Kumar; Shadbar, Qureshi Mohammed; Chavan, Nayaku; Deokar, Sarika Babasaheb; et al. (WO2012090055A1, 2012)
The invention relates to an improved process for the preparation of amino functionalized oligomeric monomeric reactant type polyimides having higher stability. More particularly it relates to a process for the preparation of soluble imide prepolymers, used as matrix resins that can be rapidly cured with multi-functional moieties such as diepoxy, dicarboxyl, anhydride, diisocyanates to form crosslinked structures having enhanced thermal stability and mechanical strength.

Ethyl oligo-silicates with strong acid heterogeneous polymeric catalysts - Bevara, Madhusudana Rao; Bhongale, Sunil Sitaram; Bhosle, Sonali Madhavrao; Chavan, Nayaku; Chelanattukizhakkemadath, Raman Rajan; Deokar, Sarika Babasaheb; Dhoble, Deepa Arun; Dwivedi, Mayank; Ghorpade, Ravindra V.; Harikrishna, Reghunathan; Dhanasekharan, Janakiraman; John, Aruldoss; et al. (WO2012056290 A1, 2012)
The present invention provides a process for the synthesis of ethyl silicate with varying silica concentration, by hydrolysing ethyl silicate in varying water concentration in the presence of sulfonated catalysts having a styrene-divinyl benzene backbone. The present invention further relates to the preparation of beaded crosslinked polymers containing sulfonic acid moieties having an interconnected pore structure and surface area up to 400 m2 /g.

Photopolymerization kinetics of 2-phenylethyl (meth) acrylates studied by photo DSC - Ghorpade, Ravindra V.; Bhosle, Sonali Madhavrao; Ponrathnam, S.; Rajan, C. R.; Chavan, Nayaku; Harikrishna, Reghunathan (Journal of Polymer Research, 2012)
The present work deals with the photopolymerization of 2-phenylethyl (meth)acrylates and estimation of their kinetic parameters. Formulations were made by independently homogenizing the monomers with photoinitiators of two different classes. Two different compositions of photoinitiators were used to study the effect of concentration of photoinitiator on cure kinetics. These compositions obtained were tested for photo curing performance using differential photocalorimetry (DPC) or photo DSC under polychromatic radiation. The heat flow against time was recorded for all formulations under isothermal conditions and the rates of polymerization as well as the percentage conversions were estimated. It was observed that due to a longer timescale for reaction diffusion, the methacrylate formulations showed a higher conversion than acrylate formulations. Other parameters such as induction time, maximum rate and conversion attained as well as the time to attain peak maximum were noted. The photopolymerization and kinetic estimations of the formulations including evaluation of kinetic models are discussed.
Keywords: Bimolecular termination model; Photo DSC; Photopolymerization; Variable autocatalytic model

Photopolymerization of bis-aromatic and alicyclic based solid urethane acrylate macromonomer in the presence of large excess of reactive diluent Kinetics and modeling - Harikrishna, Reghunathan; Ponrathnam, S.; Rajan, C. R.; Tambe, S. S. (Journal of Thermal Analysis and Calorimetry, 2013)
A solid urethane acrylate macromonomer with bis-aromatic as well as alicyclic moieties was synthesized and the kinetics of photopolymerization reactions were studied in the presence of varying concentration of photoinitiator and large excess of reactive diluent using photo DSC. The studies show that the rate of maximum polymerization was found to increase with increase in concentration of photoinitiator while a decrease was observed by an increase in temperature. The final conversion showed a decrease at highest isothermal condition due to vitrification. Estimation of kinetic parameters including applicability of autocatalytic and modified autocatalytic models were investigated by nonlinear regression. It was observed that the modified models gave a better fit with the experimental data and kinetic parameters showed a decrease with increase in temperature and an increase with increase in concentration of photoinitiator.
Keywords: Autocatalytic model; kinetics; Levenberg-Marquardt method; Photopolymerization

Kinetics of photocationically curable formulations involving glycerol diglycidyl ether and phenyl glycidyl ether - Harikrishna, Reghunathan (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2014)
Kinetic analysis of formulations based on glycerol diglycidyl ether and phenyl glycidyl ether were carried out in the presence of sulfonium salt as initiator at 35 mW cm(-2) using photo differential scanning calorimeter and the final conversion was found to increase with an increase in phenyl glycidyl ether content. The effects of formulation monomer ratios at three different temperatures were studied. The variations in the observed kinetic parameters can be related to increase in mobility of reactive species with temperature, distance of counter ion from the propagating cationic center, as well as extent of crosslinking reaction which controlled the course and duration of the reaction. The applicability of autocatalytic kinetic model was also evaluated and the system underwent early gelation and the activation energy decreased with an increase in phenyl glycidyl ether content. Analysis of stable photocured films containing glycerol diglycidyl ether and phenyl glycidyl ether showed better thermal stability than rigid films obtained with glycerol diglycidyl ether.
Keywords: autocatalytic kinetic model; Cationic photopolymerization; Glycidyl ether; Photo DSC

Photopolymerization kinetics of bis-aromatic based urethane acrylate macromonomers in the presence of reactive diluent - Harikrishna, Reghunathan; Ponrathnam, S.; Rajan, C. R. (Progress in Organic Coatings, 2014)
The present work deals with the photopolymerization of bis-aromatic based urethane acrylate macromonomers in the presence of excess end capping agent as reactive diluent and estimation of their kinetic parameters. Formulations were made by independently homogenizing the macromonomers with photoinitiators of three different classes. Three different compositions of photoinitiators were used to study the effect of concentration of photoinitiator on cure kinetics. These compositions obtained were tested for photo curing performance using photo DSC under polychromatic radiation. The heat flows against time were recorded for all formulations under isothermal condition and the rates of polymerization, peak maximum times as well as the percentage conversions were estimated. It was observed that due to a longer timescale for reaction diffusion, formulations with macromonomer containing propoxylated backbone showed higher conversions than the corresponding ethoxylated analogue. The photopolymerization and kinetic estimations of the formulations including evaluation of kinetic model are discussed. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Bimolecular termination model; kinetics; Macromonomer; Photopolymerization

Photopolymerization of high internal phase emulsions based on 2-ethylhexyl (meth)acrylates and ethylene glycol dimethacrylate - Harikrishna, Reghunathan; Shaikh, A. W.; Ponrathnam, S.; Rajan, C. R.; Bhongale, Sunil Sitaram (Designed Monomers and Polymers, 2014)
Photopolymerization of high internal phase emulsions based on 2-ethylhexyl (meth)acrylates and ethylene glycol dimethacrylate was carried out in presence of low concentration of different photoinitiators. The stable emulsions obtained by mixing with individual photoinitiators were subjected to low-intensity photopolymerization under UV-Visible lamp. Identical samples were irradiated for differing periods ranging from 2 to 10min at an interval of 2min. The percentage conversions of each monomer in the compositions with respect to the time of irradiation were determined using gas chromatography. It was observed that the formulations containing IRGACURE 819 showed the highest conversion while that containing IRGACURE 2959 showed the least conversion. The former showed high conversion due to the proximity of the absorption maxima of photoinitiator to the major emission line of mercury spectrum at 365nm while the latter showed least conversion due to non-availability of major absorption maxima within the irradiation range.
Keywords: (meth)acrylates; high internal phase emulsion; Photopolymerization; residual monomer analysis

Reaction kinetics and modeling of photoinitiated cationic polymerization of an alicyclic based diglycidyl ether - Harikrishna, Reghunathan; Ponrathnam, S.; Tambe, S. S. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 2014)
Photoinitiated cationic polymerization of cycloaliphatic diepoxides had received tremendous attention, while studies with lesser polymerizable diglycidyl ethers are comparatively less reported. The present work deals with the photoinitiated cationic polymerization of cyclohexane dimethanol diglycidyl ether followed by estimation of kinetic parameters. The effects of concentration of photoinitiator and temperature on curing performance were studied using photo differential scanning calorimeter or photo DSC with polychromatic radiation. It was observed that the rate of polymerization as well as ultimate conversion increased with increasing concentration of photoinitiator and temperature. The influences of gelation as well as diffusional restrictions have remarkable effect on cure performance. The kinetic parameters as per autocatalytic kinetic model were studied by Levenberg-Marquardt nonlinear regression method instead of conventional linear method for obtaining more accurate values of apparent rate constant. It was observed that the model fits with data from initial stages to almost towards the end of the reaction. The activation energy was found to be higher than the values reported for more reactive cycloaliphatic diepoxides. The value of pre-exponential factor increased with increase in activation energy showing influence of gelation at early stages of reaction. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Autocatalytic model; kinetics; Levenberg-Marquardt method; Photopolymerization

Ambient temperature photocopolymerization of tetrahydrofurfuryl methacrylate and isobornyl methacrylate: reactivity ratios and thermal studies - Rajdeo, K. S.; Ponrathnam, S.; Pardeshi, S.; Chavan, Nayaku; Bhongale, Sunil Sitaram; Harikrishna, Reghunathan (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2015)
Photocopolymerization of heterocyclic monomer namely, tetrahydrofurfuryl methacrylate with bulky bicyclic monomer, isobornyl methacrylate with different feed ratios was carried out in bulk with low concentration of an -hydroxyl ketone based photoinitiator. The ambient temperature photocopolymerization was carried out by using a UV-Visible lamp with fixed low intensity of 0.4mW cm(-2) for a period of 6min. The residual monomer remained in the polymerization process were determined by using gas chromatography. The reactivity ratio values for the two monomers were calculated from the copolymer composition data by using Fineman-Ross, Kelen-Tudos, Extended Kelen-Tudos and Mao-Huglin methods. Individually, as well as the average of all the methods revealed that the monomer reactivity ratios of tetrahydrofurfuryl methacrylate were higher than isobornyl methacrylate. The dyad sequence distribution and dyad sequence lengths were calculated using the Igarashi and Pyun method and the sequence length distribution for tetrahydrofurfuryl methacrylate was observed to be higher with an increase in its feed content. This supports the reactivity ratio studies that a higher monomer reactivity ratio value for tetrahydrofurfuryl methacrylate was observed as compared to its comonomer. The thermal studies showed that the glass transition temperatures of the copolymers increased with an increase in isobornyl methacrylate content.
Keywords: Copolymer; methacrylates; micro structure; photocopolymerization; reactivity ratios; thermal studies

Cationic photopolymerization kinetics of neat coating formulations involving poly(propylene glycol) diglycidyl ether and glycerol diglycidyl ether - Harikrishna, Reghunathan (Journal of Thermal Analysis and Calorimetry, 2015)
Kinetic analysis of formulations based on poly(propylene glycol) diglycidyl ether and glycerol diglycidyl ether was carried out using photodifferential scanning calorimeter. The effects of formulation monomer ratios at different temperatures were studied as photocalorimetric optimization studies of formulation ratios involving diglycidyl ethers are less reported. The nature of cure was found to depend more on the in situ physical parameters rather than on the mechanism of the reaction. The variations in the observed kinetic parameters can be related to interplay of mobility of reactive species, distance of counter ion and the diffusional restrictions. The final conversion was found to increase with increase in poly(propylene glycol) diglycidyl ether content, while the thermal stability increased with an increase in glycerol diglycidyl ether content. Autocatalytic kinetic model was also evaluated, and the system underwent early gelation. The studies show that the intermediate formulations are promising compositions for surface-coating applications.
Keywords: Coatings; Diglycidyl ether; kinetics; PhotoDSC; Photopolymerization

Inhibition effect of N,N-diglycidyl-4-glycidyloxy aniline on photosensitized cationic polymerization of formulations involving resorcinol diglycidyl ether and poly(propylene glycol)diglycidyl ether - Harikrishna, Reghunathan (Journal of Photochemistry and Photobiology A-Chemistry, 2015)
Cationic photopolymerization studies of poly(propylene glycol)diglycidyl ether with and without 25 wt% of resorcinol diglycidyl ether were carried out in presence of bis(4-methylphenyl)iodonium hexafluorophosphate as photoinitiator. Analyses were carried out using polychromatic radiation at different temperatures in a photo differential scanning calorimeter. The formulations showed an enhancement in the rate of polymerization on addition of resorcinol diglycidyl ether. The same formulations when subjected to photosensitized polymerization in presence of 1-chloro-4-propoxy-9H-thioxanthen-9-one, showed a reverse behavior in rate due to partial absorption of radiation by resorcinol diglycidyl ether. Studies carried out on by the addition of N,N-diglycidy1-4-glycidyloxy aniline as inhibitor on the photosensitized formulations showed higher scavenging activity by inhibitor. The addition of nitrogen containing epoxy monomer as inhibitor can lead to its possible crosslinking within the matrix on polymerization along with a decrease in rate of polymerization without compromising on the final observed conversion. This effect can occur readily for non vitrifying systems. Thus, this observation provides an insight into its possible usage in a rate controlled photopolymerizable epoxy formulations. The photopolymerization kinetics were found to depend on the nature of generation, propagation and scavenging of active centers which are heavily dependent on diffusional restrictions imparted by in situ viscosity of the system. The kinetic estimations as well as evaluation of autocatalytic kinetic model are investigated. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Glycidyl ether; Inhibition; kinetic model; kinetics; Photopolymerization; Photosensitization